Effectiveness of a balance training home exercise programme for adults with haemophilia: A pilot study - Hill, Keith; Fearn, M.; Williams, S.; Mudge, L.; Walsh, C.; Mccarthy, P.; Walsh, M.; Street, A. (Blackwell Publishing Ltd, 2010)
Adults with haemophilia and other bleeding disorders often develop lower limb musculoskeletal problems associated with bleeds into joints and muscles, which may affect balance performance and increase likelihood of falling. The aim of this study was to evaluate the effectiveness of an individualized balance and strength home exercise programme on improving balance and related outcomes for adults with haemophilia and other bleeding disorders. Twenty male adults with haemophilia and other bleeding disorders (mean age 39.4 years, 95% CI = 33.7-45.1) were recruited to participate. They underwent a comprehensive clinical and force platform assessment of balance and related measures. Based on assessment findings, the assessing physiotherapist provided an individualized home exercise programme of balance, strengthening and walking exercises. Re-assessment occurred after the 4-month exercise programme. Twelve participants (60%) completed the programme and were re-assessed. There were no safety problems or dropouts associated with the exercise programme aggravating joint status. Although there were no statistically significant changes in any of the measures (adjusted for multiple comparisons), there were improvements of between 5% and 22% on 10 of the 16 measures, with the Neurocom modified Clinical Test of Sensory Interaction on Balance (P = 0.036) and Timed Sit to Stand (P = 0.064) approaching significance. A tailored home exercise programme targeting balance, strengthening and walking is feasible for adults with haemophilia and other bleeding disorders. These results suggest that positive physical outcomes including improved balance and mobility may be achieved with this type of programme. © 2009 Blackwell Publishing Ltd.